Galectin-3 and Severity of Liver Fibrosis in Metabolic Dysfunction-Associated Fatty Liver Disease - Sotoudeheian, Mohammadjavad (Protein and Peptide Letters, 2024)
Metabolic dysfunction-associated Fatty Liver Disease (MAFLD) is a chronic liver disease characterized by the accumulation of fat in the liver and hepatic steatosis, which can progress to critical conditions, including Metabolic dysfunction-associated Steatohepatitis (MASH), liver fibrosis, hepatic cirrhosis, and hepatocellular carcinoma. Galectin-3, a member of the galectin family of proteins, has been involved in cascades that are responsible for the pathogenesis and progression of liver fibrosis in MAFLD. This review summarizes the present understanding of the role of galectin-3 in the severity of MAFLD and its associated liver fibrosis. The article assesses the underlying role of galectin-3-mediated fibrogenesis, including the triggering of hepatic stellate cells, the regulation of extracellular degradation, and the modulation of immune reactions and responses. It also highlights the assessments of the potential diagnostic and therapeutic implications of galectin-3 in liver fibrosis during MAFLD. Overall, this review provides insights into the multifaceted interaction between galectin-3 and liver fibrosis in MAFLD, which could lead to the development of novel strategies for diagnosis and treatment of this prevalent liver disease.
Keywords: liver steatosis